Strand 4: Chalk To Cable: Conquering the Tyranny of Distance in Australian Higher Education - Oliver, Dave; Luck, Jo-Anne; Vieth, Errol (Proceedings of the International Conference on Networked Learning, 1998)
Technologically advanced western countries have experienced great social changes since the end of world war two and higher education has been transformed. Many factors have had an influence, but the growth in technology and its social effects, along with governmental influences, appear the strongest. Higher education has changed from a small, exclusive, traditional, independent, privileged and detached sector of society, to one that is large, inclusive, innovative, regulated, open and integral. This paper explores both the social and economic trends inherent in the emergence of life long learning, and government attitudes and policy affecting advances in knowledge through the higher education sector. The paper explores the dynamics of the Australian higher education scene revolving around a case study of how a small regional higher education provider, Central Queensland University (CQU) has developed as a networked institution, becoming the first Australian University to establish campuses beyond state boundaries. The expansion of CQU from a single site serving a predominantly local population, first into distance education, to multi campus operation, to overseas and inter-state operation is traced along with the implications of this transition on networked learning. Teaching techniques available for use in these changing contexts are examined. The student profile and its reaction to networked learning environments are explored. Experiences with networked delivery of subjects using e-mail lists, web delivery and electronic assignment submission are discussed.